Question: 1
Find the zeros of each of the following quadratic polynomials and verify the relationship between the zeroes and their coefficients:
(i) f(x) = x^{2} – 2x – 8
(ii) g(s) = 4s^{2} – 4s + 1
(iii) 6x^{2} – 3 – 7x
(iv) h(t) = t^{2} – 15
(v) p(x) = x^{2} + 2√2 x – 6
(vi) q(x) = √3 x^{2} + 10x + 7√3
(vii) f(x) = x^{2}  (√3 + 1)x + √3
(viii) g(x) = a(x^{2} + 1) – x(a^{2} + 1)
Solution:
(i) f(x) = x^{2} – 2x – 8
We have,
f(x) = x^{2} – 2x – 8
= x^{2} – 4x + 2x – 8
= x (x – 4) + 2(x – 4)
= (x + 2)(x – 4)
Zeroes of the polynomials are – 2 and 4.
Now,
Hence, the relationship is verified.
(ii) g(s) = 4s^{2} – 4s + 1
We have,
g(s) = 4s^{2} – 4s + 1
= 4s^{2} – 2s – 2s + 1
= 2s(2s – 1)− 1(2s – 1)
= (2s – 1)(2s – 1)
Zeroes of the polynomials are 1/2 and 1/2.
Hence, the relationship is verified.
(iii) 6s^{2} − 3 − 7x
= 6s^{2} − 7x − 3 = (3x + 11) (2x – 3)
Zeros of the polynomials are 3/2 and (1)/3
Hence, the relationship is verified.
(iv) h(t) = t^{2} – 15
We have,
Zeroes of the polynomials are  √15 and √15
Sum of the zeroes = 0  √15 + √15 = 0
0 = 0
Hence, the relationship verified.
(v) p(x) = x^{2} + 2√2 x – 6
We have,
p(x) = x^{2} + 2√2  6
= x^{2} + 3√2x + 3√2x  6
= x(x + 3√2)  √2(x + 3√2)
= (x + 3√2)(x  √2)
Zeroes of the polynomials are 3√2 and –3√2 Sum of the zeroes
 6 = – 6
Hence, the relationship is verified.
(vi) q(x) = √3 x^{2} + 10x + 7√3
q(x) = √3x^{2} + 10x + 7√3
= √3x^{2} + 7x + 3x + 7√3
= √3x(x+√3)7(x+√3)
= (x + √3)(7 + √3x)
Zeros of the polynomials are √3 and 7/√3
Product of the polynomials are  √3, 7/√3
7 = 7
Hence, the relationship is verified.
Zeros of the polynomials are 1 and √3
Hence, the relationship is verified
(viii) g(x) = a[(x^{2} + 1)– x(a^{2} + 1)]2
= ax^{2} + a − a^{2}x − x
= ax^{2} − [(a^{2}x + 1)] + a
= ax^{2} − a^{2}x – x + a
= ax(x − a) − 1(x – a) = (x – a)(ax – 1)
Zeros of the polynomials are 1/a and 1 Sum of the zeros
Product of zeros = a/a
Hence, the relationship is verified.
Question: 2
If α and β are the zeroes of the quadratic polynomial f(x) = x^{2} – 5x + 4, find the value of
Solution:
We have,
α and β are the roots of the quadratic polynomial.
f(x) = x^{2} – 5x + 4
Sum of the roots = α + β = 5
Product of the roots = αβ = 4
So,
Question: 3
If α and β are the zeroes of the quadratic polynomial f(x) = x^{2} – 5x + 4, find the value of
Solution:
Since, α and β are the zeroes of the quadratic polynomial.
p(y) = x^{2} – 5x + 4
Sum of the zeroes = α + β = 5
Product of the roots = αβ = 4
So,
Question: 4
If α and β are the zeroes of the quadratic polynomial p (y) = 5y^{2} – 7y + 1, find the value of
Solution:
Since, α and β are the zeroes of the quadratic polynomial.
p(y) = 5y^{2} – 7y + 1
Sum of the zeroes = α + β = 7
Product of the roots = αβ = 1
So,
Question: 5
If α and β are the zeroes of the quadratic polynomial f(x) = x^{2} – x – 4, find the value of
Solution:
Since, α and β are the zeroes of the quadratic polynomial.
We have,
f(x) = x^{2} – x – 4
Sum of zeroes = α + β = 1
Product of the zeroes = αβ =  4
So,
Question: 6
If α and β are the zeroes of the quadratic polynomial f(x) = x^{2} + x – 2, find the value of
Solution:
Since, α and β are the zeroes of the quadratic polynomial.
We have,
f(x) = x^{2} + x – 2
Sum of zeroes = α + β = 1
Product of the zeroes = αβ = – 2
So,
Question: 7
If one of the zero of the quadratic polynomial f(x) = 4x^{2} – 8kx – 9 is negative of the other, then find the value of k.
Solution:
Let, the two zeroes of the polynomial f(x) = 4x^{2} – 8kx – 9 be α and − α.
Product of the zeroes = α × − α = – 9
Sum of the zeroes = α + (− α) = – 8k = 0
Since, α – α = 0
⇒ 8k = 0 ⇒ k = 0
Question: 8
If the sum of the zeroes of the quadratic polynomial f(t) = kt^{2} + 2t + 3k is equal to their product, then find the value of k.
Solution:
Let the two zeroes of the polynomial f(t) = kt^{2} + 2t + 3k be α and β.
Sum of the zeroes = α + β = 2
Product of the zeroes = α × β = 3k
Now,
Question: 9
If α and β are the zeroes of the quadratic polynomial p(x) = 4x^{2} – 5x – 1, find the value of α^{2}β + αβ^{2}.
Solution:
Since, α and β are the zeroes of the quadratic polynomial p(x) = 4x^{2} – 5x – 1
So, Sum of the zeroes α + β = 5/4
Product of the zeroes α × β = – ¼
Now,
α^{2}β + αβ^{2} = αβ (α + β)
Question: 10
If α and β are the zeroes of the quadratic polynomial
f(t) = t^{2} – 4t + 3, find the value of α^{4}β^{3} + α^{3}β^{4}.
Solution:
Since, α and β are the zeroes of the quadratic polynomial f(t) = t^{2} – 4t + 3
So, Sum of the zeroes = α + β = 4
Product of the zeroes = α × β = 3
Now,
α^{4}β^{3} + α^{3}β^{4} = α^{3}β^{3}(α + β)
= (3)^{3}(4) = 108
Question: 11
If α and β are the zeroes of the quadratic polynomial
f(x) = 6x^{2} + x – 2, find the value of
Solution:
Since, α and β are the zeroes of the quadratic polynomial f(x) = 6x^{2} + x – 2.
Sum of the zeroes = α + β = ⅙
Product of the zeroes =α × β = ⅓
Now,
By substitution the values of the sum of zeroes and products of the zeroes, we will get
=  25/12
Question: 12
If α and β are the zeroes of the quadratic polynomial f(x) = 6x^{2} + x – 2, find the value of
Solution:
Since, α and β are the zeroes of the quadratic polynomial f(x) = 6x^{2} + x – 2.
Sum of the zeroes = α + β = 6/3
Product of the zeroes = α × β = 4/3
Now,
By substituting the values of sum and product of the zeroes, we will get
Question: 13
If the squared difference of the zeroes of the quadratic polynomial
f(x) = x^{2} + px + 45 is equal to 144, find the value of p.
Solution:
Let the two zeroes of the polynomial be αand β.
We have,
f(x) = x^{2} + px + 45
Now,
Sum of the zeroes = α + β = – p
Product of the zeroes = α × β = 45
So,
Thus, in the given equation, p will be either 18 or 18.
Question: 14
If α and β are the zeroes of the quadratic polynomial
f(x) = x^{2} – px + q, prove that
Solution:
Since, α and β are the roots of the quadratic polynomial given in the question.
f(x) = x^{2} – px + q
Now,
Sum of the zeroes = p = α + β
Product of the zeroes = q = α × β
LHS = RHS
Hence, proved.
Question: 15
If α and β are the zeroes of the quadratic polynomial f(x) = x^{2} – p(x + 1) – c, show that (α + 1)(β + 1) = 1 – c.
Solution:
Since, α and β are the zeroes of the quadratic polynomial
f(x) = x^{2} – p(x + 1)– c
Now,
Sum of the zeroes = α + β = p
Product of the zeroes = α × β = ( p – c)
So,
(α + 1)(β + 1)
= αβ + α + β + 1
= αβ + (α + β) + 1
= (− p – c) + p + 1
= 1 – c = RHS
So, LHS = RHS
Hence, proved.
Question: 16
If α and β are the zeroes of the quadratic polynomial such that α + β = 24 and α – β = 8, find a quadratic polynomial having α and β as its zeroes.
Solution:
We have,
α + β = 24 …… E1
α – β = 8 …. E2
By solving the above two equations accordingly, we will get
2α = 32 α = 16
Substitute the value of α, in any of the equation. Let we substitute it in E2, we will get
β = 16 – 8 β = 8
Now,
Sum of the zeroes of the new polynomial = α + β = 16 + 8 = 24
Product of the zeroes = αβ = 16 × 8 = 128
Then, the quadratic polynomial isK
x2– (sum of the zeroes)x + (product of the zeroes) = x^{2} – 24x + 128
Hence, the required quadratic polynomial is f(x) = x^{2} + 24x + 128
Question: 17
If α and β are the zeroes of the quadratic polynomial
f(x) = x^{2} – 1, find a quadratic polynomial whose zeroes are
Solution:
We have,
f(x) = x^{2} – 1
Sum of the zeroes = α + β = 0
Product of the zeroes = αβ = – 1
From the question,
Sum of the zeroes of the new polynomial
{By substituting the value of the sum and products of the zeroes}
As given in the question,
Product of the zeroes
Hence, the quadratic polynomial is
x^{2} – (sum of the zeroes)x + (product of the zeroes)
= kx^{2} – (−4)x + 4x^{2} –(−4)x + 4
Hence, the required quadratic polynomial is f(x) = x^{2} + 4x + 4
Question: 18
If α and β are the zeroes of the quadratic polynomial f(x) = x^{2} – 3x – 2, find a quadratic polynomial whose zeroes are
Solution:
We have,
f(x) = x^{2} – 3x – 2
Sum of the zeroes = α + β = 3
Product of the zeroes = αβ = – 2
From the question,
Sum of the zeroes of the new polynomial
So, the quadratic polynomial is,
x^{2} (sum of the zeroes)x + (product of the zeroes)
x^{2}  (sum of the zeroes)x + (product of the zeroes)
Hence, the required quadratic polynomial is k
Hence, the required quadratic polynomial is k
Question: 19
If α and β are the zeroes of the quadratic polynomial f(x) = x^{2} + px + q, form a polynomial whose zeroes are (α + β)^{2} and (α – β)^{2}.
Solution:
We have,
f(x) = x^{2} + px + q
Sum of the zeroes = α + β = p
Product of the zeroes = αβ = q
From the question,
Sum of the zeroes of new polynomial = (α + β)^{2} + (α – β)^{2}
= (α + β)^{2} + α^{2} + β^{2} – 2αβ
= (α + β)^{2} + (α + β)^{2} – 2αβ – 2αβ
= ( p)^{2} + ( p)^{2} – 2 × q – 2 × q
= p^{2} + p^{2}^{ }– 4q
= p^{2} – 4q
Product of the zeroes of new polynomial = (α + β)^{2} (α – β)^{2}
= ( p)^{2}(( p)^{2}  4q)
= p^{2} (p^{2}–4q)
So, the quadratic polynomial is,
x^{2} – (sum of the zeroes)x + (product of the zeroes)
= x^{2} – (2p^{2} – 4q)x + p^{2}(p^{2} – 4q)
Hence, the required quadratic polynomial is f(x) = k(x^{2} – (2p^{2} –4q) x + p^{2}(p^{2}  4q)).
Question: 20
If α and β are the zeroes of the quadratic polynomial f(x) = x^{2} – 2x + 3, find a polynomial whose roots are:
(i) α + 2,β + 2
(ii)
Solution:
We have,
f(x) = x^{2} – 2x + 3
Sum of the zeroes = α + β = 2
Product of the zeroes = αβ = 3
(i) Sum of the zeroes of new polynomial = (α + 2) + (β + 2)
= α + β + 4
= 2 + 4 = 6
Product of the zeroes of new polynomial = (α + 1)(β + 1)
= αβ + 2α + 2β + 4
= αβ + 2(α + β) + 4 = 3 + 2(2) + 4 = 11
So, quadratic polynomial is:
x^{2} – (sum of the zeroes)x + (product of the zeroes)
= x^{2} – 6x +11
Hence, the required quadratic polynomial is f(x) = k(x^{2} – 6x + 11)
f(x) = k(x^{2} – 6x + 11)
(ii) Sum of the zeroes of new polynomial
Product of the zeroes of new polynomial
So, the quadratic polynomial is,
x^{2} – (sum of the zeroes)x + (product of the zeroes)
Thus, the required quadratic polynomial is f(x) = k(x^{2} – 23x + 13)
Question: 21
If α and β are the zeroes of the quadratic polynomial f(x) = ax^{2} + bx + c, then evaluate:
(i) α – β
(iv) α^{2}β + αβ^{2}
(v) α^{4} + β^{4}
Solution:
f(x) = ax^{2} + bx + c
Here,
Sum of the zeroes of polynomial = α + β = b/a
Product of zeroes of polynomial = αβ = c/a
Since, α + β are the roots (or) zeroes of the given polynomial, so
(i) α – β
The two zeroes of the polynomials are 
From the previous question, we know that,
Also,
αβ = c/a
Putting the values in E.1, we will get
Since,
Sum of the zeroes of polynomial = α + β = – b/a
Product of zeroes of polynomial = αβ = c/a
After substituting it in E1, we will get
(iv) α^{2}β + αβ^{2}
= αβ(α + β) …….. E 1.
Since,
Sum of the zeroes of polynomial = α + β = – b/ a
Product of zeroes of polynomial = αβ = c/a
After substituting it in E1, we will get
(v) α^{4} + β^{4}
= (α^{2} + β^{2})^{2} – 2α^{2}β^{2}
= ((α + β)^{2} – 2αβ)^{2} – (2αβ)^{2} ……. E 1
Since,
Sum of the zeroes of polynomial = α + β = – b/a
Product of zeroes of polynomial = αβ = c/a
After substituting it in E1, we will get
Since,
Sum of the zeroes of polynomial = α + β = – b/a
Product of zeroes of polynomial = αβ = c/a
After substituting it, we will get
Since,
Sum of the zeroes of polynomial = α + β = – b/a
Product of zeroes of polynomial = αβ = c/a
After substituting it, we will get
Since,
Sum of the zeroes of polynomial= α + β = – b/a
Product of zeroes of polynomial= αβ = c/a
After substituting it, we will get
126 videos477 docs105 tests

1. What are polynomials? 
2. How do you determine the degree of a polynomial? 
3. Can a polynomial have more than one variable? 
4. What are the different types of polynomials based on the number of terms? 
5. How can polynomials be used to solve reallife problems? 

Explore Courses for Class 10 exam
